2012
DOI: 10.1186/1471-2202-13-47
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-rich saline alleviates early brain injury via reducing oxidative stress and brain edema following experimental subarachnoid hemorrhage in rabbits

Abstract: BackgroundIncreasing experimental and clinical data indicate that early brain injury (EBI) after subarachnoid hemorrhage (SAH) largely contributes to unfavorable outcomes, and it has been proved that EBI following SAH is closely associated with oxidative stress and brain edema. The present study aimed to examine the effect of hydrogen, a mild and selective cytotoxic oxygen radical scavenger, on oxidative stress injury, brain edema and neurology outcome following experimental SAH in rabbits.ResultsThe level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 63 publications
0
61
0
Order By: Relevance
“…Our group has previously reported that HS may attenuate neuronal apoptosis via Akt/GSK3β pathway and inhibit vasospasm by limiting vascular inflammation and oxidative stress post-SAH [37]. Other studies also demonstrated similar beneficial effect of HS treatment in experimental SAH model [38][39][40]. Nevertheless, so far it was unclear whether HS could influence NLRP3 inflammasome and attenuate EBI after SAH.…”
Section: Introductionmentioning
confidence: 89%
“…Our group has previously reported that HS may attenuate neuronal apoptosis via Akt/GSK3β pathway and inhibit vasospasm by limiting vascular inflammation and oxidative stress post-SAH [37]. Other studies also demonstrated similar beneficial effect of HS treatment in experimental SAH model [38][39][40]. Nevertheless, so far it was unclear whether HS could influence NLRP3 inflammasome and attenuate EBI after SAH.…”
Section: Introductionmentioning
confidence: 89%
“…The apoptotic cells were detected by TUNEL staining, which was performed according to our previous study. 31 An in situ cell death detection kit, POD (ISCDD, Boehringer Mannheim) was used. Briefly, the formalinfixed tissues were embedded in paraffin and sectioned at 4-mm thicknesses with a microtome.…”
Section: Staining Methodsmentioning
confidence: 99%
“…Tissue sections were stained with cresyl violet (Nissl) as previously described. 31 The 4-mm sections were hydrated in 1% toluidine blue for 10 minutes. After washing with double-distilled water, they were dehydrated and mounted with Permount.…”
Section: Staining Methodsmentioning
confidence: 99%
“…The Nissl staining procedure was performed according to procedures described previously (Zhuang et al, 2012).…”
Section: Nissl Staining Analysismentioning
confidence: 99%